Mycenaeans in Croatia? - Tomas, Helena (Array, 2005)
The article examines a possible Mycenaean presence along the Croatian coast and its vicinity. Although Mycenaean allegations have been proposed for several artefacts and sites, it is shown that such intepretations are often unfounded. It is concluded that the Mycenaean traces in Croatia are doubtful.